2005
DOI: 10.1002/da.20054
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mood-congruent false and true memory recognition in depression

Abstract: The present study investigated the extent of mood-congruent false and true memory recognition in depression. A group of 25 patients with depression and 28 healthy controls completed a variant of the Deese-Roediger McDermott task. Four lists were read to participants in sequence, followed by a recognition task. The words in each list were associated with a central but unmentioned theme word that was either depression-relevant (i.e., loneliness), delusion-relevant (betrayal), positive (holidays), or neutral (win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Consistent with some of this speculation, previous research has found that participants with depression make more (although not significantly more) false recognition errors with emotional words, particularly for depression-relevant words, despite learning emotional material as well as non-depressed participants (Moritz et al, 2005). Interestingly, Moritz, Voight, Arzola, and Otte (2008) examined word lists that possessed individual salience for participants.…”
Section: Theoretical and Methodological Issues When Examining False Mmentioning
confidence: 68%
See 1 more Smart Citation
“…Consistent with some of this speculation, previous research has found that participants with depression make more (although not significantly more) false recognition errors with emotional words, particularly for depression-relevant words, despite learning emotional material as well as non-depressed participants (Moritz et al, 2005). Interestingly, Moritz, Voight, Arzola, and Otte (2008) examined word lists that possessed individual salience for participants.…”
Section: Theoretical and Methodological Issues When Examining False Mmentioning
confidence: 68%
“…First, some of the discrepancies between studies investigating false memory and mood could have arisen because of the nature of the depressed population. For example, Torrens et al (2008) used dysphoric student participants who were not diagnosed with a MDD whereas Moritz et al (2005) used a sample of inpatients with a primary diagnosis of MDD and Joormann et al (2009) used a sample of outpatients diagnosed with MDD. The current study used strict criteria when defining our participants with depression.…”
Section: Theoretical and Methodological Issues When Examining False Mmentioning
confidence: 99%
“…A negative bias in remembering past events has been explained by the mood congruent memory effect, which describes a biasing of the selection of memories in the direction of the present mood. Evidence gathered with clinically depressed patients and word learning tasks for explicit memory, however, has provided mixed results [e.g., Bradley et al, 1995, for positive, andEllwart et al, 2003;Moritz et al, 2005, for negative findings]. A possible explanation may be the use of isolated words, which may lead less consistently to emotional involvement than, for example, stories, which did produce a mood congruent memory bias even in a non-clinical sample of children with depressed mood [Bishop et al, 2004].…”
Section: Negative Biasmentioning
confidence: 98%
“…In depressed mood states, the accessibility of mood-congruent material is increased, enabling those with a depressed mood to have improved memory for negatively valenced emotional material, compared with neutral material. However, while depressed individuals tend to remember negatively valenced emotional material as well as nondepressed individuals, they demonstrate impaired memory for neutral material (207). Individuals with depression have difficulty removing irrelevant negative material from their working memory (139,143,207).…”
Section: Reproductive Steroids: Regulators Of Affective State Affectimentioning
confidence: 99%